The productivity of White Fulani (Bunaji) cattle in pastoralist herds of the Kaduna Plains, Nigeria - Otchere, E.O. (International Livestock Centre for Africa, 1982)
Presents results of a field data collection as to sizes & structure of herds, reproductive performance, i.e. age-at-first-calving, calving percentage, seasonality of calving, and weights of cows, and birth weights, growth rates and weaning age & weights of calves in two Fulani pastoralist herds at Abet & Kurmin Biri, Kaduna, Nigeria, as well as results of trials to study the performance, in terms of total milk yield, milk offtake, and birth weight & weight gain during first 90 days of calves, of Bunaji cows fed supplements of cotton seed cake in the dry season.